The Potential Hepatoprotective Effect of Vinpocetine against Lead-Induced Inflammatory and Apoptotic Cytokines in Rats - Manal Abdulkhaliq Ibrahim; SARAH OMRAN; Noora S. Ghalib; Nada N. Al-Shawi (College of Pharmacy University of Baghdad, 2024)
Abstract Environmental pollution with heavy metals like lead has become a matter of concern, the accumulation and multi-systemic toxicity of lead affect most body organs and its toxicity is related with many pathological changes, especially on liver. 18 Sprague-Dawley rats weighting 160-250g of both male and female were included; the animals were divided with randomness into three groups, 6 rats each group: 1st group: Rats were orally inoculated with 0.3 ml saline, after 1 hour, intraperitoneal (IP) injection of 100 μl of saline was given (Control). 2nd group: Rats received daily IP injection (20 mg/kg body wt.)  of immediately preparation lead acetate for 5 days, the dose and route of administration were chose based on previous research. 3rd group Rats in this group received vinpocetine and lead as the following; at first vinpocetine administered orally by gavage tube in a dose of 3mg / kg every day for five days alone and then lead injection started in a dose of 20 mg/kg and continued for 10 days with oral vinpocetine dose where vinpocetine administered 1hr before lead. After 24 hrs (end of management period), each rat was anesthetized by diethyl ether. Liver homogenates were done; then interleukin-1 beta (IL-1β), interleukin-10 (IL-10), tumor necrosis factor-alpha (TNF-α) and caspase 3 were estimated. Lead was significantly (P < 0.05) raised IL-1beta, TNF-α and caspase 3, whereasit significantly (P < 0.05) reducedIL-10 levels. On the other hand, vinpocetine significantly (P < 0.05) lowered IL-1beta, caspase 3 and it significantly (P < 0.05) raised IL-10 but it didn't significantly (P > 0.05) reduce TNF-α. Vinpocetine may have potential hepatoprotective effect against lead-induced toxicity. Keywords: Apoptotic, Hepatoprotective, Inflammation, Lead, Vinpocetine.